2009
DOI: 10.1016/j.metabol.2009.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine acutely activates 5′adenosine monophosphate–activated protein kinase and increases insulin-independent glucose transport in rat skeletal muscles

Abstract: Caffeine (1,3,7-trimethylxanthine) has been implicated in the regulation of glucose and lipid metabolism including actions such as insulin-independent glucose transport, glucose transporter 4 expression, and fatty acid utilization in skeletal muscle. These effects are similar to the exercise-induced and 5'adenosine monophosphate-activated protein kinase (AMPK)-mediated metabolic changes in skeletal muscle, suggesting that caffeine is involved in the regulation of muscle metabolism through AMPK activation. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 40 publications
1
89
0
Order By: Relevance
“…It has been shown by us and others that caffeine-induced increases in Ca 2ϩ signaling regulate substrate metabolism, possibly via AMPK activation (1,6,22,35). Indeed, we have shown that when CaMKII or CaMKK was inhibited during caffeine stimulation, there were subsequent decreases in AMPK␣ 2 activity along with decreases in the rates of FA uptake, glucose uptake, and FA oxidation (1,35).…”
Section: Discussionmentioning
confidence: 57%
“…It has been shown by us and others that caffeine-induced increases in Ca 2ϩ signaling regulate substrate metabolism, possibly via AMPK activation (1,6,22,35). Indeed, we have shown that when CaMKII or CaMKK was inhibited during caffeine stimulation, there were subsequent decreases in AMPK␣ 2 activity along with decreases in the rates of FA uptake, glucose uptake, and FA oxidation (1,35).…”
Section: Discussionmentioning
confidence: 57%
“…Our results suggest that caffeine administration restored Glut4 expression in the elderly group, but it was not able to increase Glut4 expression above a maximal level in the 12 M group. The mechanism by which caffeine increases Glut4 expression is still unclear, but the effect appears to be extant to several cell types: rat skeletal muscle primary cultures (Egawa et al 2009) and myoblasts (Mukwevho et al 2008), although contrasting results have been obtained in adipose tissue cells where caffeine suppressed insulininduced Glut4 translocation (Akiba et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…AMPK also decreases hepatic glucose production and increases glucose uptake in skeletal muscle, playing an important role in glucose homeostasis, and AMPK activation in the pancreatic beta cell decreases insulin secretion (Long and Zierath 2006). Recently, it has been shown that caffeine can increase Glut4 mRNA in skeletal muscle cells and insulinindependent glucose transport through an AMPKmediated process (Egawa et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In ex vivo skeletal muscle incubation, some groups reported that caffeine decreased insulin sensitivity and glucose transport by inhibiting insulin signaling (16)(17)(18) (17). At present, there has been no report that caffeine has a positive effect on insulin signaling.…”
Section: Discussionmentioning
confidence: 99%